Does Living Outside of a Major City Impact on the Timeliness of Chlamydia Treatment? A Multicenter Cross-Sectional Analysis. Issue 8 (August 2016) - Foster, Rosalind; Ali, Hammad; Crowley, Margaret; Dyer, Roisin; Grant, Kim; Lenton, Joanne; Little, Christine; Knight, Vickie; Read, Phillip; Donovan, Basil; McNulty, Anna; Guy, Rebecca
Abstract : Background: Timely treatment of Chlamydia trachomatis infection reduces complications and onward transmission. We assessed client, process, and clinic factors associated with treatment delays at sexual health clinics in New South Wales, Australia. Methods: A retrospective review of 450 consecutive clients with positive chlamydia results (not treated at the time of the consultation) was undertaken at 6 clinics (1 urban, 3 regional, and 2 remote) from October 2013. Mean and median times to treatment were calculated, overall and stratified by process steps and clinic location. Results: Nearly all clients (446, 99%) were treated, with 398 (88%) treated in ⩽14 days and 277 (62%) in ⩽7 days. The mean time-to-treatment was 22 days at remote clinics, 13 days at regional and 8 days at the urban clinic ( P < 0.001). Mean time between the laboratory receipt of specimen and reporting of result was 4.9 in the remote clinics, 4.1 in the regional, and 2.7 days in the urban clinic ( P < 0.001); and the mean time between the clinician receiving the result until client treatment was15, 5, and 3 days ( P < 0.01), respectively. Conclusions: At participating clinics, treatment uptake was high, however treatment delays were greater with increasing remoteness. Strategies to reduce the time-to-treatment should be explored such as point-of-care testing, faster specimen processing, dedicated clinical time to follow up recalls, SMS results to clients, and taking treatment out to clients. Abstract : A study of chlamydia time-to-treatment in Australia found that treatment delays increased with geographical remoteness. Attending a remote clinic was independently associated with a time-to-treatment of >7 days.